The validity and reliability of the EValuation of INtervention Scale: preliminary report. (31st March 2016) - Warren, Inga; Hicks, Beverley; Kleberg, Agneta; Eliahoo, Joseph; Anand, Kanwaljeet J. S.; Hickson, Mary
Abstract: Aim: Pain management is a priority for infants receiving neonatal care as they undergo many necessary painful and stressful interventions, which are associated with negative short‐ or long‐term consequences. This study aims to validate the content, and test the reliability, of the EValuation of INtervention Scale (EVIN), which is designed to evaluate the use of widely recommended nonpharmacological strategies to reduce neonatal pain and stress during procedures. Methods: The content of the EVIN was validated with multidisciplinary participation (N = 80), and consistency was established via observations on preterm infants (N = 12, at 31–34 weeks' gestation) during interventions in a neonatal unit. A revised scale was tested for inter‐rater reliability with observations of invasive (blood sampling, N = 16) and noninvasive (nappy change, N = 18) interventions. The intraclass correlation coefficient (ICC) was used to determine inter‐rater reliability. SPSS (PASW Statistics) version 18 was used for analysis. Results: Very good intraclass correlation coefficients (>0.8) for both invasive (0.962) and noninvasive procedures (0.970) were achieved. Conclusion: These results indicate that the EVIN is suitable for the evaluation of nonpharmacological support during painful or stressful interventions.